Resveratrol and Malignancies - Bunaciu, Rodica P. (Curr Pharmacol Rep, 2015)
Carcinogenesis is a multifactorial process, frequently encompassing 3 stages: initiation, promotion and progression. It is characterized by multiple deviations from normal both at the cell and organism levels. Although most people have a small number of cells that present deviations from normal, most of those cells will not cause cancer. However, some will. What tips the balance between normal and abnormal is the subject of intense scientific research as well as unfounded speculations. Chronic inflammation is one of the risk factors for cancer. Resveratrol is consumed by the population as a dietary supplement in the hope of decreasing the risk of inflammation and cancer and other chronic diseases such as diabetes and vascular diseases. There is a discrepancy between the doses used in the animal studies showing that resveratrol decreases all three stages of carcinogenesis, and the doses ingested by the population either as supplements or in the diet. While there is health benefit from using high resveratrol doses, it might be also of practical and scientific benefit to focus future effort in understanding the effects of normal dietary resveratrol levels.